Virulence factors and phylogenetic group profile of uterine Escherichia coli in early postpartum of high-producing dairy cows - De Cássia Bicudo, Luana [UNESP]; Oba, Eunice [UNESP]; Bicudo, Sony Dimas [UNESP]; Da Silva Leite, Domingos; Siqueira, Amanda Keller; De Souza Monobe, Marina Mitie [UNESP]; Nogueira, Meghi; De Figueiredo Pantoja, José Carlos [UNESP]; Listoni, Fernando José Paganini [UNESP]; Ribeiro, Márcio Garcia [UNESP] (CSIRO Publishing, 2019)
Escherichia coli is the most common contaminant of the bovine uterus in the first few weeks postpartum, and one of the most important pathogens involved in uterine infections. This bacterium is characterised by diverse virulence factors (VF) however, the profile of E. coli VF in physiologic postpartum uterine contamination is not well established. Therefore, the present study aimed to investigate the prevalence of intrauterine bacteria, a set of virulence factors and phylogroups of E. coli isolates, leukogram and uterine cytology in 75 Holstein cows at 24 h (Sampling time 1) and 14 days (Sampling time 2) postpartum. Escherichia coli, α-haemolytic Streptococcus, Trueperella pyogenes, and Pasteurella multocida were the most common microorganisms isolated in pure culture, whereas E. coli and Clostridium perfringens Type A, E. coli and α-haemolytic Streptococcus, and E. coli and Proteus mirabilis were the most frequent microorganisms in mixed colonies at both studied sampling times. In the 59 E. coli isolates after 24 h (n = 35) and 14 days (n = 24) postpartum, the genes detected for VF were fimH, iucD/aer, kps, hlyA, usp, vt1 and vt2. Most E. coli strains detected in both moments of study belonged to Commensal phylogenetic groups A and B1, whereas Pathogenic groups D and B2 were identified at 24 h and 14 days postpartum respectively. All cows presented suitable immune response against the presence of bacteria in uterine lumen, observed by leukocytosis, neutrophilia, lymphocytosis and monocytosis at leukogram and a high number of polymorphonuclear leukocytes in uterine cytology, in both studied moments. Thus, a complex diversity of aerobic and anaerobic bacteria is involved in uterine contamination in the early postpartum of cows, besides the predominance of E. coli. Moreover, the genes fimH, iucD/aer, hlyA, kps, usp, vt1 and vt2 play a key role in the virulence of E. coli in this period.
Keywords: animal reproduction; bacteriology; genetic variation; microbial diversity